PERUT SINCAN (Snakes and Ladders Game of Disaster Mitigation) as a Disaster Education Learning Medium - Siska Dwi Utami; Hapsari’ati Mustari (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The Indonesian people really need insight into disaster mitigation, especially strengthening disaster mitigation which is one form of implementation of the 2030 Sustainable Development Goals (SDGs) goal 13. Disaster mitigation can basically be implanted through education. Disaster mitigation education from an early age, especially in elementary schools, is needed to form a generation of young Indonesians who are resilient to disasters. So that interactive learning media is needed, one of which is a game of snake and ladder modified with disaster mitigation material. This innovation is called PERUT SINCAN (Disaster Mitigation Snake Game) which has 25 posts containing challenges with disaster materials. The formulation of the problem is the concept of implementation, implementation, and implications of the SINCAN STATE. The research method used is descriptive method using qualitative data. Data collection techniques using data analysis techniques from related literature. With this interactive learning media, it is hoped that it can add insight and raise awareness of the importance of disaster mitigation in children.